Four cases of neoplasia in amphibians at two zoological institutions: Alpine newt Ichthyosaura alpestris, Red‐eyed tree frog Agalychnis callidryas, Common frog Rana temporaria and Puerto Rican crested toad Peltophryne lemur. Issue 1 (17th April 2017) - O'Brien, M. F.; Justice, W. S. M.; Beckmann, K. M.; Denk, D.; Pocknell, A. M.; Stidworthy, M. F.
Abstract : Four cases of spontaneous neoplasia in different species of Amphibia at two zoological collections in the United Kingdom (2009–2016) are described: disseminated lymphosarcoma with leukaemia in an Alpine newt Ichthyosaura alpestris, nasal adenocarcinoma in a Red‐eyed tree frog Agalychnis callidryas, pulmonary carcinoma in a Common frog Rana temporaria and cutaneous mast‐cell tumour in a Puerto Rican crested toad Peltophryne lemur . History, and gross and histological findings are presented. In particular, mast‐cell tumours in Anura and respiratory tumours of amphibians have rarely been reported. Abstract : Four cases of spontaneous neoplasia in different species of Amphibia at two zoological collections in the United Kingdom (2009–2016) are described: disseminated lymphosarcoma with leukaemia in an Alpine newt Ichthyosaura alpestris, nasal adenocarcinoma in a Red‐eyed tree frog Agalychnis callidryas, pulmonary carcinoma in a Common frog Rana temporaria and cutaneous mast‐cell tumour in a Puerto Rican crested toad Peltophryne lemur . History, and gross and histological findings are presented. In particular, mast‐cell tumours in Anura and respiratory tumours of amphibians have rarely been reported.(Ventral thoracic mass in Common frog Rana temporaria . Photo: Katie M. Beckmann, WWT Slimbridge)